2013
DOI: 10.7314/apjcp.2013.14.5.2829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Audit in Radiation Oncology: Results from One Academic Centre in Delhi, India

Abstract: The objective was to analyze the radiotherapy (RT) practice at the cancer centre of a tertiary academic medical institution in Delhi. This audit from an Indian public institution covered patient care processes related to cancer diagnosis, integration of RT with other anti-cancer modalities, waiting time, overall treatment time, and compliance with RT. Over a period of one year, all consecutively registered patients in radiotherapy were analyzed for the audit cycle. Analysis of 1,030 patients showed median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…47 For example, a study in New Delhi reported a median of 41 days from registration to radiation therapy initiation; 25% of patients did not complete therapy. 48 Many African countries, including Cameroon, Rwanda, and South Africa, have reported an interval of up to 7 months between request for care as a result of symptoms and treatment of cancer. 41,49,50 Although more than half of the population in less-developed countries reside in rural areas, 51 oncology services tend to exist in urban areas.…”
Section: Resources Currently Available In Lower-resource Settingsmentioning
confidence: 99%
“…47 For example, a study in New Delhi reported a median of 41 days from registration to radiation therapy initiation; 25% of patients did not complete therapy. 48 Many African countries, including Cameroon, Rwanda, and South Africa, have reported an interval of up to 7 months between request for care as a result of symptoms and treatment of cancer. 41,49,50 Although more than half of the population in less-developed countries reside in rural areas, 51 oncology services tend to exist in urban areas.…”
Section: Resources Currently Available In Lower-resource Settingsmentioning
confidence: 99%
“…Head-and-neck cancer (HNC) is the most common malignancy in India, and 83% of patients present with Stage III and IV HNC. [ 1 ] Radiation therapy (RT) is the most commonly used and effective cancer-directed therapy for advanced HNC. In modern oncology practice, combined modality therapy (CMT) is the mainstay of cancer management.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the key factors that are assessed include compliance to RT, waiting time for RT, intention of treatment, effect on overall treatment time and the integration with allied cancer modalities. 11 Thus, an audit has the potential to improve overall RT practice, specifically in developing countries such as India with an aim to improve treatment outcomes. 11 There are several reasons for unwanted interruptions in planned RT.…”
Section: Introductionmentioning
confidence: 99%